Quantitative determination of quaternary solid waste-based binders and its hydrates by XRD - Wang, Jixiang; Xiang, Li; Ren, Caifu; Huang, Tianyong; Zhu, Yingcan; Wei, Peng; Wang, Dongmin; Liu, Ze (Construction & building materials, 2024)
Solid waste-based binders offer intrinsic low-carbon advantages and non-primary resource consumption, making them one of the most promising low-carbon binders. However, the compositions of multiple components and the complex nature of their raw materials—mainly industrial solid wastes—make the stability and control of their quality very difficult, thereby limiting their practical applications in industry. The core of controlling product stability lies in quantifying the blended mixes. The progress in X-ray diffraction and its analysis methods has provided an opportunity to directly and non-destructively measure the phase compositions of solid waste-based binders. Rietveld refinement has been widely used to quantify the blend of crystals. However, due to the X-ray amorphous diffraction characteristics of aluminosilicates in most solid wastes, distinguishing and quantifying them is challenging. The PONCKS method has provided a strategy for indexing the amorphous phases and facilitating the distinction of different amorphous phases in various raw materials. In this study, by combining the Rietveld and PONCKS methods, a strategy has been presented that applies the XRD method to quantify the mixing proportions and their hydration products, and its validity has been verified. Factors such as crystal preferred orientation, background selection, and the structure for establishing the CASH model have been identified as more significant for accurate analysis and the optimal fitting strategy has been suggested. Lastly, in-situ XRD measurements, a very promising technology for studying the fresh paste hydration processes, have also been conducted. The real-time continuous determination has provided a more insightful understanding of the hydration and setting behaviors of the solid waste-based binder. [Display omitted] •The combination of Rietveld and PONCKS analysis shown promising potential in quantification of solid waste-based binders.•Preferred orientation, background fitting, and CASH model are more significant factors for accurate analysis.•In-situ XRD measurement present insights for understanding the hydration processes.